The student edition of SIMULINK - MathWorks, Inc. (Englewood Cliffs, NJ : Prentice Hall, 1996)
An interactive workbench to model, analyze, and simulate physical and mathematical systems. An intuitive block-diagram interface lets user model simple and complex dynamical systems; choose from a set of integration methods to simulate user's system; and apply the analysis tools in SIMULINK and MATLAB to analyze and improve the simulation.
Title from disk label.
0
Keywords: Computer simulation -- Software